Enhancing National Climate Services (ENACTS) approach to support climate resilience in agriculture. - Dinku, Tufa; Hansen, James; Rose, Alison; Damen, Beau; Sheinkman, Michael (2018)
Many opportunities to improve agricultural resilience to a variable and changing climate depend on access to high-quality local climate records and are constrained by data gaps. Addressing data quality of meteorological station observations. The ENACTS approach builds capacity of a National Meteorological Service (NMS) to produce higher quality historical climate data in gridded format, ready for use by the agriculture sector for modeling and/or mapping. The ENACTS approach involves collaboration with NMS to apply quality-control methods to available station data and to blend that station data with satellite measurements and reanalysis products using the IRI Climate Data Tools (CDT). The resulting gridded data products combine the benefits of high quality station data with the spatial and temporal coverage of satellite and reanalysis data products. The quality of ENACTS data products is higher than global gridded datasets because additional station data has been incorporated. Online “Map-rooms” support access to a range of derived climate information products and tools. ENACTS has already enabled 11 African countries and 2 regional centers to improve their climate services. The IRI Climate Data Tool and the ENACTS approach also offer a proven solution to needs identified in Asia and the Pacific.